Overview of preclinical and phase II clinical studies on Pegmolesatide’s long-term erythropoiesis stimulating effect via EPOR-mediated signal transduction - Xiaoying Ma; Zhen Li; Lu Zhang; Hui Qian; Qinkai Chen; Ye Tao; Yunfan Li; Dandan Wang; Zhizhen Hu; Weili Luo; Ping Li; Hai Yu; et al. (Journal of Translational Medicine)
Abstract Introduction Anemia is a prevalent complication of chronic kidney disease (CKD), primarily due to insufficient erythropoietin (EPO). Pegmolesatide (by Hansoh Pharma) is currently the only marketed long-acting EPO mimetic peptide (EMP) for the treatment of anemia in both dialysis and non-dialysis CKD patients. This paper aimed to explore the long-acting erythropoiesis stimulating molecular mechanism of Pegmolesatide. Methods In vitro assays were utilized to assess Pegmolesatide erythropoietin receptor (EPOR) affinity, competitive binding, cell proliferation/survival, apoptosis, cell surface receptor expression, and signal transduction. Pharmacokinetics (PK) and Pharmacodynamics (PD) parameters were evaluated in BALB/c mice following single administration. Furthermore, two Phase II clinical trials in dialysis and non-dialysis chronic kidney disease (CKD) patients with anemia, respectively CTR20140533 and CTR20140539, assessed PK-PD and safety following repeated administration. Results In vitro Pegmolesatide demonstrated enhanced binding stability and prolonged residency at EPOR, surpassing erythropoiesis-stimulating agents (ESAs) rHuEPO and Darbepoetin. This sustained EPOR binding facilitated heightened endogenous EPOR expression post-drug withdrawal, maintaining downstream signal transduction pathways (JAK2/STAT5, ERK1/2 MAPK) for erythropoiesis. Pegmolesatide promoted UT-7 cell proliferation & survival and suppressed apoptosis. Following a single 0.08 mg/kg dose of Pegmolesatide in BALB/c mice, reticulocyte count, red blood cells, hemoglobin, and hematocrit persisted at elevated levels 4-6 days after administration. In the two clinical Phase II studies dose-dependent increases in hemoglobin and prolonged response duration were independently observed. Pegmolesatide showed significant PK-PD dual prolongation effects and was well tolerated. Adverse events were mild and manageable, with no reports of severe anaphylaxis. Discussion Preclinical and clinical evidence signifies that Pegmolesatide is a unique, potent PEGylated EPO-memetic peptide (EMP) with a prolonged PD efficacy and PK half-life and a good safety-tolerability profile. To elucidate further, future studies will address the endocytosis, intracellular degradation, and ligand release of EPOR subsequent to Pegmolesatide binding, thereby supplementing our understanding of the molecular mechanism at play. Trial registration: Phase IIa clinical study of Pegmolesatide on renal anemia, CTR20140533. Initial Public Notice 14 Jan 2015, http://www.chinadrugtrials.org.cn/clinicaltrials.searchlistdetail.dhtml . Phase II clinical study of Pegmolesatide on renal anemia, CTR20140539. Initial Public Notice 26 Jan 2015, http://www.chinadrugtrials.org.cn/clinicaltrials.searchlistdetail.dhtml .